Food Safety Assurance: Effect of Hygiene Sanitation practices on Quality Service and Tourist Satisfaction in Culinary Tourism Area of Kampung Ujung, Labuan Bajo - Berybe, Gregorius Antariksa; Umul, Dewi Sartika; Dae, Yohana Etheldreda Ine (PT. Hafasy Dwi Nawasena, 2023)
The principle of Sanitation Hygiene is an important factor in the operation of food and drink services to ensure service quality from the perspective of hygiene and food safety. Culiner managers not only understand the principles of sanitary hygiene but also its application in its services. This study focused on two things, namely analyzing the effect of Sanitation and hygiene on Service Quality and Visitor Satisfaction in Kampung Ujung Culinary Tour, Labuan Bajo. This research is quantitative research with 100 tourists/visitors to Kampung Ujung Labuan Bajo culinary tourism, as research respondents. Data testing (Outer and Inner Model) using SEM PLS software version 4.0. The results of data processing research show that sanitation has a positive (path coefficient, 0.769) and significant (P-value 0.00) effect on service quality. Hygiene has a positive effect (path coefficient, 0.183) but is not significant (P-value 0.052) on service quality. Service quality has a positive (path coefficient, 0.860) and significant (P-value 0.00) effect on satisfaction. Sanitation has a positive (path coefficient, 0.661) and significant (P-value 0.00) effect on satisfaction through service quality. Hygiene has a positive effect (path coefficient 0.158) but not significant (P-value 0.048) on satisfaction through service quality. Based on the results of the study, cleanliness, especially sanitation of culinary areas, needs to be improved. The higher or better the sanitation of Kampung Ujung Culinary Tourism, the higher the quality of service shown and affects the level of satisfaction of tourists who visit and vice versa.